(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
Distance education has moved from a pandemic-era stopgap to a permanent pillar of higher education in emerging digital economies, yet quality assurance frameworks have not kept pace with the speed of adoption or with the arrival of artificial intelligence in the learning workflow. This paper proposes an AI-ready quality-assurance (QA) methodology for distance higher education in Uzbekistan, built on the international Educational Organizations Management System standard ISO 21001 and aligned with UNESCO’s human-centred guidance for AI in education. We combine a documentary review of national reform instruments with a maturity-assessment instrument applied across six management domains, and we illustrate the approach with a simulated multi-institution pilot. The results indicate that a standards-based, AI-ready QA cycle can raise course-completion, assessment-validity and learner-satisfaction indicators while narrowing the urban–rural readiness gap that characterises the sector. We argue that quality assurance, rather than technology procurement, is the binding constraint on credible distance education in emerging economies, and we offer a concrete, auditable methodology that ministries and universities can adopt.